Estudo da composição química e da atividade antibacteriana in vitro e em alimento do óleo essencial de Cróton blanchetianus Baill - Melo, Geiseanny Fernandes do Amarante (2011)
Considering the search on new antimicrobial substances from natural fonts, the Croton blanchetianus Baill (marmeleiro) appears as an aromatic plant distributed on tropical and subtropical regions and it possess some biological activities. In this study, the essential oil from the Croton blanchetianus Baill leaves was evaluated with the objective of identifying its chemicals constituents and analyse its antibacterial activity in vitro against micro-organisms, and in model food (pieces of meat). The extraction of the essential oil from Croton blanchetianus Baill was realized through the process of hydrodistillation and chemical composition analysis by gas chromatography-mass spectrometry (GC-MS). To the physicalchemical characterization of the essential oil was determined the relative density, refractive index, solubility in alcohol, color and appearance. The evaluation of antibacterial activity of this essential oil against micro-organisms of interest on food was realized through the plate diffusion method with inhibition zones and determination of Minimum Inhibitory Concentration (MIC) was shown through the technique of broth macrodilution, while the interference of the essential oil in the in vitro microbial death kinetics and its model meat was realized through a count of viable cellular. It was identified 14 constituents in a complex mixture of monoterpenes (59.43%) and sesquiterpenes (40.56%). The main components found on the leaves were limonene (25.70%), α-pinene (16.32%) and bicyclogermacrene (13.00%). The antibacterial evaluation showed an activity against three strains L. monocytogenes, A. hydrophila and S. Enteritidis. The values of MIC and MBC of the essential oil oscillated from 1.25 to 40 μg.mL-1 and 2.5 to 80 μg.mL, respectively. The results found in the death kinetics showed a bactericidal effect to Aeromonas hydrophila and Listeria monocytogenes and bacteriostatic to Salmonella Enteritidis. It was observed a bacteriostatic effect in all concentration of the essential oil tested on contaminated meat with L. monocytogenes. These results show the potentiality of the essential oil extracted from the leaves of C. Blanchetianus Baill as an alternative font of a natural antimicrobial for use in food conservation system.